Tradisi Pesta Panen Makjene-Jene Terhadap Kesejahteraan Masyarakat Siawung Barru - Fitriana Gaffar,; Hasaruddin, (Jurnal Berita Sosial, 2022)
The contribution of the makjene-jene harvest party tradition is a classic for the activities of the Siawung Barru community. This type of research is qualitative by using a communication approach and a sociological approach. The data sources for this research are traditional leaders, community leaders, mosque imams, and youth leaders and books related to this research. While the method of data collection is done by means of interviews, observation and documentation. Data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation and conclusion drawing. The results of this study indicate that the Makjene-jene tradition must still be carried out because if the harvest party ceremony is not carried out it will get a disaster and strange things will occur. Therefore, this tradition is still carried out because it is a rejection of reinforcements. The harvest party tradition is still celebrated because it is a place that can increase social relations and solidarity that has been carried out by all levels of society. While the implementation of the Makjene-jene tradition is a form of gratitude to God Almighty for the success of the harvest.